2020
DOI: 10.1183/13993003.03448-2020
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnoea, lung function and CT findings 3 months after hospital admission for COVID-19

Abstract: The long-term pulmonary outcomes of coronavirus disease 2019 (COVID-19) are unknown. We aimed to describe self-reported dyspnoea, quality of life, pulmonary function, and chest CT findings three months following hospital admission for COVID-19. We hypothesised outcomes to be inferior for patients admitted to intensive care units (ICU), compared with non-ICU patients.Discharged COVID-19-patients from six Norwegian hospitals were consecutively enrolled in a prospective cohort study. The current report describes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
372
5
14

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 294 publications
(420 citation statements)
references
References 24 publications
29
372
5
14
Order By: Relevance
“…The patient-reported outcomes and lung function after hospitalization for COVID-19 (PROLUN) study invited subjects 4-8 weeks after being discharged from a COVID-19related hospital stay to participate in a follow-up study with electronic or paper questionnaires and a clinical visit about 3 months after discharge [9]. The present study includes only subjects discharged before 1 June 2020, and who resided in the catchment area of Akershus University Hospital and Østfold Hospital Trust Kalnes.…”
Section: Survey Of Hospitalized Subjectsmentioning
confidence: 99%
“…The patient-reported outcomes and lung function after hospitalization for COVID-19 (PROLUN) study invited subjects 4-8 weeks after being discharged from a COVID-19related hospital stay to participate in a follow-up study with electronic or paper questionnaires and a clinical visit about 3 months after discharge [9]. The present study includes only subjects discharged before 1 June 2020, and who resided in the catchment area of Akershus University Hospital and Østfold Hospital Trust Kalnes.…”
Section: Survey Of Hospitalized Subjectsmentioning
confidence: 99%
“…In our 10-week follow-up study of 220 patients with COVID-19 pneumonia, pulmonary restriction was found to be the most prevalent pulmonary function impairment [ 1 ]. Probably in part as a result of restriction, reductions in diffusing capacity (TL CO ) have been demonstrated in smaller cohorts [ 2 , 3 , 4 , 5 ]. These tended to be associated with disease severity [ 2 , 3 ] and residual CT abnormalities [ 4 ], but not with symptoms nor ICU admission [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probably in part as a result of restriction, reductions in diffusing capacity (TL CO ) have been demonstrated in smaller cohorts [ 2 , 3 , 4 , 5 ]. These tended to be associated with disease severity [ 2 , 3 ] and residual CT abnormalities [ 4 ], but not with symptoms nor ICU admission [ 5 ]. Most post-COVID-19 follow-up studies are limited to three months, prompting the question whether a favorable evolution in lung function and/or radiological abnormalities is to be expected beyond 3 months.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging reports demonstrate persistent symptoms and lung function impairment in COVID-19 survivors discharged from hospital (1)(2)(3)(4)(5)(6). However, little is known about the longer-term impact of COVID-19 in patients not requiring hospitalization.…”
mentioning
confidence: 99%